BRAND TRUST AS CELEBRITY ENDORSER MARKETING MODERATOR'S ROLE - Febrian, Angga; Fadly, Muhtad (Jurnal Aplikasi Manajemen, 2021)
Celebrity endorsement is a form of marketing communication done both online and offline as it creates a positive brand attitude. However, its effectiveness in influencing customers' purchase decision needs to be considered. This quantitative research took the sample from 249 respondents who experience in shopping and comprehend the role of celebrity endorsement. The SmartPLS 3.0 was used in data analyzing techniques, and bootstrap testing was also employed. The results show that celebrity endorsement affects customers' attitudes, but it does not affect their purchasing behavior. Adding brand trust as a moderator variable enhances the influence of celebrity endorsement on brand attitude. Therefore, marketers need to be able to see how big brand trust is owned before deciding to use celebrity endorsement to market their product. Future researchers can apply models in cultures of other countries and focus on the profile of specific celebrities so that the results can be generalized more.